Biodegradación del malatión utilizando microorganismos nativos de suelos agrícolas (2009)
ABSTRACT: The degradation of the malathion pesticide by native microorganisms in an agricultural soil was studied in both laboratory and field conditions. The field study was conducted in a specific area in Caldas (municipality located in the south of the valle de Aburrá, department of Antioquia, Colombia) designated for dairy cattle and vegetable crop. Malathion disappearance and the formation of its main metabolite (malaoxon) were quantified utilizing an analytical method that included a soil sample extraction and pesticide and metabolite quantification by gas chromatography. The extraction was conducted by mechanical shaking with ethyl acetate, and the quantification was performed using a chromatographer connected to a micro-electron capture detector with an automatic injection system. Recoveries were 89.4% for malathion and 93.8% for malaoxon. In the laboratory (35 days, 2.50 µg/g of soil), malathion degradation was 81.6%. 51.3% of this value corresponded to microbial degradation, and the rest was due to losses associated with physicochemical processes. Under field conditions (21 days, 1.50 µg/g), an average degradation of 74.8% was obtained. Counting of soil microorganisms was 6.8 x 105 CFU/g soil.